TEKNOLOGI INFORMASI DAN KINERJA USAHA MIKRO KECIL DAN MENENGAH - AMELIA SETYAWATI (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2020)
Micro small medium enterprises (MSME) are the backbone of the Indonesian economy, and even the world. The purposed of this study was to test empirically the effect of information technology on performances MSME sector food and beverage industry in Bandung Raya. The research used explanatory research to clarify the relationship between the study variables and test hypotheses. The sampling technique used is random sampling proportionate area. The sample used in the study amounted to 152 owners of MSME. The results of the study are significant effect on the performances MSME of information technology. Information. Technology information related skills during this covid-19 pandemic are very important for the survival of the community. Not only can it be used for business, but also to support distance learning and another activities.